Genetic complementation analysis in Pycnoporus cinnabarinus - V. Cifuentes; G. Hermosilla; G. Pincheira (Fungal Genetics Reports, 1993)
White-rot basidiomycetes are known as very powerful degraders of wood components. The relative enzyme activities during the degrading process may vary between different species.